Lets fly high Intermediate English For Officers Iefo training - Fatimah, Ali; Nur Syafawati, Sabuan (PBM News, 2022)
17 August 2022 – A spectacular event held on 15th August 2022 was marked as the officiating ceremony of Lets’ Fly High, an Intermediate English for Officers (IEFO) Training organised by the Centre for Modern Languages (CML).